Analysis of key parameters influencing the permeability of cement sheath based on multiphysical fields - Luo Wei; Weidong Zhang; Kewei Xu; Jingwei Yang; Yangyang Liu; Wei Xiao; Mingji Wei; Liqin Qian; Chengyu Xia (PLoS ONE, 2025)
This paper develops a finite element analysis model to investigate the seepage characteristics of cement sheaths, considering the flow properties of their porous medium. The model’s applicability under various conditions was evaluated through grid sensitivity tests and model validation, indicating that it effectively captures the seepage behavior of cement sheaths with a reasonable degree of reliability. Key parameters, including cement sheath length, permeability, gap structure, pressure differential, and fluid properties, were analyzed using finite element methods to determine their impact on seepage flow. The findings reveal that crack width, permeability, and cement sheath length significantly influence seepage flow in both liquid and gas media. These insights enhance the understanding and prediction of cement sheath seepage characteristics under diverse conditions.